Analysis of the Public Policy Formulation Process in Educational Institutions (Formulation, Agenda Arrangement and Ratification) - Dede Ridho Firdaus; Anis Fauzi; Ahmad Qurtubi (Journal of Educational Analytics, 2023)
This study aims to explain the policy formulation process as it relates to the position of education in the context of the public sector, which must be managed seriously, and the level of urgency for the government in setting program priorities such as development. This study used qualitative research methods with a literature study approach. Several stages of data presentation are applied in this paper, namely data restatement, description to map data patterns, and interpretation to highlight the definite meaning of the policy formulation process in educational institutions, including formulation, agenda setting, and ratification.